Legal Certainty and Economic Resilience of MSMEs Post-Disaster Based on Society 5.0 in Palu City - Restutanti Borman; Nur Zaitun Humairo; Melinda Huwindra; Oktavia Ramadani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the role of legal certainty in strengthening the economic resilience of Micro, Small, and Medium Enterprises (MSMEs) after disasters in Palu City and formulate a legal certainty model based on Society 5.0. The earthquake, tsunami, and liquefaction disasters in 2018 caused economic and institutional problems for MSME actors, especially damage to business premises, loss of legal documents, unclear asset status, weak business legality, and limited access to financing. This research uses an empirical legal method with a juridical-sociological approach and institutional economics. Data was obtained through document studies, regulatory studies, MSME data analysis, and limited interviews with elements of agencies, villages, and MSME actors in the Kaomona City Forest area. The results of the study show that legal certainty plays a role as a prerequisite for the economic resilience of MSMEs through the legalization of business premises, asset protection, ease of licensing, business data collection, and access to financing. Empirical findings show that there is government intervention through the provision of around 300 stalls, the existence of 264 business actors in 2021, and assistance to 185 MSME actors. However, business sustainability still faces obstacles in the form of limited integrated data, unclear regional management, low legal-digital literacy, and suboptimal technological adaptation. This research offers a model of legal certainty based on Society 5.0 through the digitization of MSME data, integration of licensing services, legalization of business premises, the use of big data, digital legal services, and strengthening the human resource capabilities of MSME actors. This model is expected to contribute to the recovery of MSMEs after disasters that is adaptive, inclusive, transparent, and sustainable.